1992
DOI: 10.1139/e92-096
|View full text |Cite
|
Sign up to set email alerts
|

Crustal temperatures near the Lithoprobe Southern Canadian Cordillera Transect

Abstract: Heat flow and radioactive heat generation have been measured and the data compiled across southern British Columbia in the region of the Lithoprobe Southern Canadian Cordillera Transect. Heat flow in the trench-arc zone between the continental margin and the Garibaldi volcanic belt is very low, but in the volcanic belt it is high and very irregular. Farther inland, to the east, the heat flow is moderately high, with the highest values in southeastern British Columbia, associated with high surface radioactive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 39 publications
6
60
0
Order By: Relevance
“…In addition to the large reflective bands beneath Vancouver Island, smaller but very "bright" reflectors have been observed at shallower depths beneath the mainland (Cook et al, 1988). Lewis et al (1992) tried to correlate these bright spots with fluids in the crust. The shallow low V p region in the tomographic image may indicate the presence of hot fluids such as melts or water in the crust, perhaps driven by a lower crustal magma intrusion.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the large reflective bands beneath Vancouver Island, smaller but very "bright" reflectors have been observed at shallower depths beneath the mainland (Cook et al, 1988). Lewis et al (1992) tried to correlate these bright spots with fluids in the crust. The shallow low V p region in the tomographic image may indicate the presence of hot fluids such as melts or water in the crust, perhaps driven by a lower crustal magma intrusion.…”
Section: Resultsmentioning
confidence: 99%
“…Surface heat flow for the warm slab models shown in Figure 6 compared with observations at northern Cascadia. Small black dots, white circles, squares, and the grey triangle are heat flow values obtained from bottomsimulating reflectors, marine probes, shelf wells, and an ODP borehole, respectively [Davis et al, 1990;Lewis et al, 1992;Hyndman et al, 1993;Wang et al, 1995]. Grey circles are heat flow observations complied by Currie et al depths than shown in Figure 6.…”
Section: Slab Dehydration and Mantle Wedge Serpentinizationmentioning
confidence: 99%
“…The heat flow decreases inland of the trench as a result of the heat sink of the cold upper part of the oceanic plate that is underthrusting the margin (e.g., Hyndman and Wang, 1993;Wang et al, 1995). Heat flow data are available from land boreholes and petroleum exploration wells on the continental shelf (Lewis et al, 1988(Lewis et al, , 1991, marine probe measurements on the continental slope and Cascadia Basin Spence et al, 2000b;Riedel, 2001;Riedel et al, 2006), and from the depth of the BSR on the continental slope Ganguly et al, 2000;Riedel, 2001;He et al, 2003).…”
Section: Riedel Et Al Gas Hydrate On the Northern Cascadia Marginmentioning
confidence: 99%